The use of resilience engineering tools for fault propagation mitigation in sociotechnical systems - Volken, Felipe Gilberto Bratti; Rosário, Claudio Roberto do (Revista Gestão da Produção Operações e Sistemas, 2021)
Purpose – To demonstrate an application of resilience engineering, aiming to improve productivity and quality by decreasing variability and fault propagation in the production functions of a sociotechnical system, the object of the study, in an asphalt concrete production plant. Design/methodology/approach – The approach used was the functional resonance analysis method, where experts in sociotechnical systems were interviewed, eliciting their knowledge on the aspects of interaction between production functions. The elicited knowledge was entered into FRAM Model Visualizer 0.4.1 software, which presents a graphical map of the system and allows the number of couplings (NC) to be analyzed. Findings – The analysis of the NCs highlighted that the laboratory control, burner, drum dryer, and baghouse functions showed a high potential for variability absorption, while the PLC control system and laboratory control functions have a high potential for fault propagation. Both groups were examined and measured explored within the scope of resilience engineering that enhance their roles in mitigating resilience within the system. Originality/value – The replication of the resilience engineering discussed in this article enables gains in productivity and quality in sociotechnical systems for the same segment; the application of the functional resonance analysis methodology demonstrated can benefit further studies on productive systems with interaction between people and technology. Keywords - Resilience engineering, productive systems, sociotechnical systems, FRAM.